(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Technology has been vastly used in learning context for the purpose of enhancing students’ learning performance. The integration of computer in language teaching and learning is growing. In particular, the computer game-based student response systems such as Kahoot! application is implemented by some educators in their teaching classesto improve students’ learning experience. Meanwhile, collaborative learning plays an important role in teaching and learning practice. Thus, this paper aims to examine the use of Kahoot! application integrated with collaborative learning approach influences the learning experiences of Japanese students in English language classroom. An experimental research approach was conducted to study how Kahoot! application is affecting the learning experiences of Japenese students. Student engegement observation checklist and feedback form were used as the research instruments in this study. The population comprised 20 Japanese students who enrolled in English language classroom participated in this experiment. The findings show that Kahoot! integrated with collaborative learning approach made positive impact on students by contributing to better engagement and enhanced learning experience of students. This study can be a reference for instructors who plan to implement game-based student response systems and collaborative learning in English language classroom.